THREE DIMENSIONAL MODELING FOR DISTRIBUTION OF DISSOLVED MERCURY (HG) IN KAPUAS ESTUARY - Nur Fathya, Edistri
Study of the distribution of mercury in the Strait of Karimata is done by modeling three-dimensional (3D) baroclinic mode by Kämpf (2010), supported by field data around the Karimata Strait. Input on the river is the transport of dissolved Hg and 1-D flow in the Kapuas River. Simulations carried out with the generating tides, winds, and the difference in density, for 15 days in June 2010, which is considered representative of conditions in the southeast monsoon. Surface currents in the Karimata Strait moving toward the north in June with an average of 0.5 m/s. Current movement is influenced by tides, wind, and density difference. Surface density in the north Karimata is bigger than in the south. Verification of surface density shows error 0,13% for coastal region and 1,43% for estuary. High density water around 1015-1016 kg/m3enter the river up to 5 km in Kapuas River and 2,5 km in Kakap River. Simulation of transport Hg shows movement of Hg toward estuary due to difference magnitude of current, when high tide 0,3 m/s and low tide 0,1 m/s.